PENGARUH KOMITMEN KEPALA SEKOLAH DAN MOTIVASI GURU TERHADAP PRODUKTIVITAS SEKOLAH DI SMAN KOTA PONTIANAK - Diana Sari; Sukmawati Sukmawati; Muhammad Chiar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to reveal: (1) the influence of the principal's commitment to schoolproductivity at State Senior High Schools in Pontianak, (2) the influence of teachermotivation on school productivity at State Senior High Schools in Pontianak, and (3)The effect of the principal's commitment and teacher motivation together on schoolproductivity at State Senior High Schools in Pontianak. This form of research usesquantitative research methods with a questionnaire as a means of collecting data. Thesubjects of this study were state senior high school teachers in Pontianak who connected92 people with civil servant teachers, had an educator certificate, had a minimum workperiod of 5 years, and had a minimum qualification of Bachelor Degree. Hypothesistesting in this study used multiple linear regression analysis using the SPSS 25application help for windows. The results of the analysis showthat: (1) there is an effectof the influence of the principal's influence on school productivity at state senior highschools in Pontianak with a value of 22.4%, (2) there is an effect of teacher motivationon school productivity at state senior high schools in Pontianak with a value of 58 , 1%,and (3) there is an effect of the influence of the principal and teacher motivationsimultaneously on school productivity at senior high schools in Pontianak with a valueof 51.3%. The implication of this research can be used as input in increasing theproductivity of schools in state senior high schools in Pontianak.Keywords: Commitment, Motivation, School Productivity